Reproductive performance and body condition score of Deccani sheep during various physiological stages in different farming systems - KOCHEWAD, S A; TRAGHUNANDAN; RAO, KSARJAN; REDDY, K KONDAL; KUMARI, NNALINI; RAMANA, DBV; KUMAR, SANJEEV; MEENA, L R; SINGH, S P (The Indian Journal of Animal Sciences, 2018)
The research was carried out to study the effect of different farming systems on reproductive traits and body condition score in Deccani sheep. Ewes (36), 9–12 months of age, were divided in to 3 groups, viz. intensive (T1), semi-intensive (T2) and extensive farming system (T3) with 12 ewes in each group following completely randomized design. The results revealed that, body weight at puberty in intensive group (17.6 kg) was significantly higher than extensive (16.3) group. Age at puberty in extensive group was significantly higher (338 days) than intensive group (290 days). The conception rate in intensive group was 75%, which was higher than semi-intensive and extensive (58.3 and 66.6% respectively). Intensive group had achieved significantly higher body weight at lambing (24.74 kg) than semi-intensive (23.12 kg) and extensive (22.23 kg). Birth weight of lambs in intensive group (2.5 kg) was significantly higher than semi-intensive (1.98 kg) and extensive groups (1.82 kg). Length of estrus cycle and duration of oestrus differed nonsignificantly in different farming systems. BCS values were significantly higher during pregnancy in intensive group. BCS near parturition (48 h near) and BCS 3 months (post-parturition) was significantly higher in intensive as compared to semi-intensive and extensive. BCS (48 h after parturition) was significantly higher in intensive and semi-intensive systems with respect to extensive system. It can be concluded that reproductive traits and body condition score were higher in intensive system compared to other systems because care of life stages through provision of concentrate feed, with minimal body energy loss can be assured in intensive farming system.